Particulate matter – a cancerous threat to our health? - Jasiura, Adam; Lipczyńska, Wiktoria; Warchoł, Konrad; Gorzel, Mateusz; Justyńska, Agata; Krafzik, Hanna; Stępień, Przemysław; Kasprzak, Hubert (Journal of Education, Health and Sport, 2023)
Introduction: Particulate matter (PM) as a part of outdoor air pollutants are classified as human carcinogens. They are formed majorly as a result of combustion process by industry, power plants and engines. PM can be divided by the size of their particles into PM2.5 and PM10, where PM2.5 are small enough to penetrate into the alveoli sacs in the lung reaching the bloodstream, whereas PM10 affect mostly oral cavity, nose and the throat. Aim of the study: This study aims to investigate the impact of PM2.5 and PM10 particle concentrations in the EU NUTS 2 subregions on the death rates due to the most common malignant neoplasms. Results: There is a positive moderate correlation (r = 0.421; p < 0.001) between the annual mean concentration of PM2.5 and deaths due to malignant tumors. The strongest correlation was observed for malignant neoplasms of larynx, which is a positive correlation with a strong effect (r = 0.641; p < 0.001); and malignant neoplasm of bladder (r = 0.523; p < 0.001). For PM10, there is a moderately weak positive correlation (r = 0,195; p = 0.008) between the annual average concentration of PM10 and deaths due to malignant tumors. The strongest correlation was observed for malignant neoplasms of larynx, which is a positive correlation with a strong effect (r = 0,551; p < 0.001). Conclusion: The effect of PM impact on the malignant neoplasms is strong to moderate. The most affected neoplasm site are the ones the PMs intake occurs, being in the respiratory system. However other sites, where PMs can accumulate can be impacted as well. Further studies about the population with the highest risk due to the PMs exposure may be beneficial as other non-air quality-connected predictors may be found.